Reggio Emilia: a postmodern approach to early childhood education - Seyyed Amir Ghasemtabar (Journal of Philosophical Investigations, 2022)
The current research was conducted with the aim of explaining and interpreting the approach of Reggio Emilia based on the basic assumptions and beliefs of postmodern philosophy. Analytical-inferential method was used to conduct the research. The scope of the current research was all national and international written sources in the field of postmodern education and the Reggio Emilia approach, from which the most reliable sources were selected using a targeted sampling method. To answer the research question, the basic principles and features of Reggio Emilia's approach were described, explained and interpreted based on the four core features of postmodern philosophy. The first feature of postmodern philosophy (denying the centrality of the knowing agent) based on the concept of " progettazione", and paying attention to the teacher as a partner, nurturer and guide and not an omniscient; The second feature of postmodern philosophy (attention to language) based on the idea of "one hundred languages of children"; The third feature of postmodern philosophy (negation of totalitarianism) is based on challenging the idea of the transferability of the curriculum, paying attention to children's meaning-making skills, rejecting the idea of homogenization and dualistic thinking, and being based on inclusive education; And finally, the fourth characteristic of postmodern philosophy (paying attention to the element of otherness) was analyzed and interpreted based on the two concepts of "listening pedagogy" and "pedagogical documentation". Imitating or copying, Reggio Emilia's approach is neither possible nor desirable. However, knowing and analyzing the features and values governing this approach can bring valuable lessons for the reconstruction and reform of early childhood education in our country.